PEMETAAN DAN MODEL KEBUTUHAN LITERASI KEUANGANG UMKM DI KECAMATAN TEMBALANG - Jati Handayani; Aris Sunindyo; Teguh Budi Santosa; R. Gunawan Setianegara; Septian Yudha Kusuma (Politeknik Negeri Semarang, 2023)
UMKM are really need financial literacy in order to be able to manage and make wise business financial policy decisions. Central Java's financial literacy index ranges from conventional to sharia 47.58 percent, 11.78 percent. This study aims to find out how to map and model financial literacy in UMKM in Tembalang District. This research includes all UMKM in Tembalang District. By using non-probability purposive random sampling of customers. Respondents are UMKM actors who had KTPsin the Tembalang District. In this study, a sample of 97 UMKM respondents was taken in Tembalang District. Data analysis in this study was carried out descriptively using SPSS software. focuses on mapping financial information to the community and the need for financial literacy, especially UMKM in Tembalang District. The highest level of financial literacy is in Banking with a score of 44, and the lowest in Islamic finance is 10. The five financial literacy needs of the financial industry and banks for UMKM consist of Savings, KUR, UMi Financing, Profit Sharing Financing and Credit. Others Cash Flow and Income Statement